The Influence of Work Motivation and Organizational Culture on Commitment Organization in Improving Employee Performance - Hermawati, Hermawati; Yusup, Yusup; Supardi, Supardi (Sebatik, 2024)
This research was conducted at the Kampar Regency Trade, Cooperatives, and Micro Small Enterprises Service, located on Jalan Jendral Sudirman No. 11, Bangkinang District. The study aims to examine and analyze the following: 1)The influence of motivation on organizational commitment, 2) The influence of organizational culture on organizational commitment, 3) The direct influence of motivation on employee performance, 4) The direct influence of organizational culture on employee performance, 5) The influence of organizational commitment on employee performance, 6) The indirect influence of motivation on employee performance through organizational commitment, 7) The indirect influence of organizational culture on employee performance through organizational commitment. This research utilizes both primary and secondary data collected through questionnaires, interviews, observations, and research documentation. The study population consists of all 48 employees of the Kampar Regency Trade, Cooperatives, and Micro Small Enterprises Service, with the entire population used as the sample. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software version 3.0, applying a 5% significance level. The findings reveal that: 1) Motivation significantly affects organizational commitment, 2) Organizational culture significantly affects organizational commitment, 3) Motivation does not directly affect employee performance, 4) Organizational culture directly affects employee performance, 5) Organizational commitment significantly affects employee performance, 6) Motivation indirectly affects employee performance through organizational commitment, 7) Organizational culture indirectly affects employee performance through organizational commitment. This research highlights the importance of motivation, organizational culture, and commitment in enhancing employee performance at the Kampar Regency Trade, Cooperatives, and Micro Small Enterprises Service.